PJJ: Mengikis Pendidikan Karakter - Nurlaila Rayantini (Balai Diklat Keagamaan Banjarmasin, 2021)
The implementation of PJJ during the Covid-19 Pandemic has a bad impact because gradually some good habits/characters in students begin to decrease. Character education that is integrated with subjects during the implementation of PJJ cannot be given or absorbed by students as expected. This study aims to obtain concrete data about the decline in the quality of Character Education during the implementation of PJJ which was extracted from the parents of students to further try to find solutions to these problems. This research uses survey research method. The population of this research is parents who have children who are still in elementary/middle level in Hulu Sungai Selatan Regency. A sample of 155 people. The results of the study are statements from parents of students, namely: Children are accustomed to getting up early in the morning 94.8%, Children get up early alone 78.7%, Children are accustomed to worshiping together 74.2%, Children are given routine responsibilities every day 85.2 %, Children shake hands if they want to leave the house 89.7%, Children help with homework every day 69%, Children are required to repeat the lessons they get every day 62.6%, Parents can be good teachers for their children 53.5%, Learning from home has been effective 23.9%, Children can learn on their own without direct guidance from the teacher 13.5%, Parents have enough time to control children's mastery of the subject matter given by the teacher 30.3%, Ensure children do not use cellphones for personal gain in addition to learning 30.3%, children using cellphones to play online games 60.6%, children enthusiastic about participating in PJJ 48.4%, PJJ being applied continuously 12.3%, agreeing PJJ to be continued 14.8%.